in Quantitative Aptitude edited by
144 views
3 votes

The value of the sum $7 \times 11 + 11 \times 15 + 15 \times 19 + \dots$ + $95 \times 99$ is

  1. $80707$
  2. $80773$
  3. $80730$
  4. $80751$
in Quantitative Aptitude edited by
by
12.8k points 250 1881 2459
144 views

1 Answer

1 vote

Let $ S = 7 \times 11 + 11 \times 15 + 15 \times 19 + \dots + 95 \times 99$

We can write first series as :

$ S_{1} = \underbrace{7 + 11 + 15 + \dots + 95}_{\text{Arithmetic Progression (AP)}}$

Here, first term $ a = 7,$  common difference $d = 11 – 7 = 4,$  last term $l = 95$

The $n^{th}$ term of the series $t_{n} = l = a+(n-1)d \;,$ where $n =$ number of terms

$ \Rightarrow 95 = 7+(n-1)4 $

$ \Rightarrow 4n – 4 + 7 = 95 $

$ \Rightarrow 4n + 3 = 95 $

$ \Rightarrow 4n = 92 $

$ \Rightarrow \boxed{ n= 23} $

The $n^{th}$ term of the series $\boxed{t_{n} = 4n + 3} $

Similarly, we can write second series as :

$S_{2} = \underbrace{11 + 15 + 19 + \dots + 99}_{\text{Arithmetic Progression (AP)}}$

Here, $ a = 11, \; d = 15 – 11 = 4, \; l = 99, \; n = 23 $

The $n^{th}$ term of the series $ t_{n} = l = a + (n-1)d $

$ \Rightarrow t_{n} = 11 + (n-1)4 $

$ \Rightarrow t_{n} = 11 + 4n – 4 $

$ \Rightarrow \boxed{t_{n} = 4n + 7} $

Now, we can write  $T_{n} = (4n+3)(4n+7) \;, \text{where} \; n = 1, 2, \dots, 23 $

$ \Rightarrow T_{n} = 16n^{2} + 28n + 12n + 21 $

$ \Rightarrow T_{n} = 16n^{2} + 40n + 21 $

$ \Rightarrow \sum T_{n} = \sum (16n^{2} + 40n + 21) $

$ \Rightarrow S_{n} = 16 \sum n^{2} + 40 \sum n + 21 \sum 1 $

$ \Rightarrow S_{n} = 16 \left[ \frac{n(n+1)(2n+1)}{6} \right] + 40 \left[ \frac{n(n+1)}{2} \right] + 21n $

 The sum of  the series $S = 16 \left[\frac{(23)(24)(47)}{6} \right] + 40 \left[ \frac{(23)(24)}{2} \right] + 21 \times 23 $

$ \Rightarrow S = 69184 + 11040 + 483 $

$ \Rightarrow \boxed{S = 80707} $

Correct Answer $: \text{A}$

$\textbf{PS :}$

If $ S_{n} = 1 + 2 + 3 + \dots + n $

$ \Rightarrow S_{n} = \displaystyle{}\sum_{k=1}^{n} k $

$ \Rightarrow \boxed{S_{n} = \frac{n(n+1)}{2}} $

If $S_{n} = 1^{2} + 2^{2} + 3^{2} + \dots + n^{2} $

$ \Rightarrow S_{n} = \displaystyle{}\sum_{k=1}^{n}k^{2} $

$ \Rightarrow \boxed{S_{n} = \frac{n(n+1)(2n+1)}{6}} $

If $S_{n} = 1^{3} + 2^{3} + 3^{3} + \dots + n^{3} $

$ \Rightarrow S_{n} =   \displaystyle{}\sum_{k=1}^{n} k^{3} $

$ \Rightarrow \boxed{S_{n} = \left[ \frac{n(n+1)}{2} \right]^{2}} $

Reference: https://brilliant.org/wiki/sum-of-n-n2-or-n3/

edited by
by
4k points 3 6 24
Answer:

Related questions

2 votes
1 answer
2
jothee asked in Quantitative Aptitude Mar 20, 2020
179 views
jothee asked in Quantitative Aptitude Mar 20, 2020
by jothee
12.8k points 250 1881 2459
179 views
Ask
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true